Education and the Traveller Community - O'Reilly, Michael (REACH: Journal of Inclusive Education in Ireland, 1996)
The Report of the 1995 Government Task Force on the Travelling Community recommended the establishment of a Traveller Education Unit within the Department of Education which would have a wide ranging remit for drafting policy, designing in-service programmes, promoting research and monitoring progress. As important as service provision, however, is the adoption by all schools of a positive approach to intercultural issues embracing the concerns of the Traveller community.